1997
DOI: 10.1097/00005373-199701000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Posttrauma Thromboembolism Prophylaxis

Abstract: The ability to identify a population with a high incidence of thromboembolism by using the RAPT score to detect asymptomatic DVT, and the suggested advantage of low molecular weight heparin, all support the need for an appropriately powered randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(156 citation statements)
references
References 14 publications
8
143
1
4
Order By: Relevance
“…None of the papers described that their randomisation process was concealed, providing a further methodological weakness as an additional source of allocation bias [31,32]. Finally, Greenfield et al [19] concluded that based on the literature, they suggested that a DVT rate of 15% in a trauma population would require a sample size of 2,500 patients to detect a reduction in DVT to 7%. Since none of the studies reviewed based their sample sizes on power calculations, there is a possibility that these studies committed a type II statistical error [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the papers described that their randomisation process was concealed, providing a further methodological weakness as an additional source of allocation bias [31,32]. Finally, Greenfield et al [19] concluded that based on the literature, they suggested that a DVT rate of 15% in a trauma population would require a sample size of 2,500 patients to detect a reduction in DVT to 7%. Since none of the studies reviewed based their sample sizes on power calculations, there is a possibility that these studies committed a type II statistical error [32].…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the demographic characteristics of the cohorts recruited in these reviewed papers is presented as Table 2. Three studies were excluded on final appraisal [18,19]. Stannard et al's [18] study was excluded since whilst the study reported that their cohort of high-energy multi-trauma patients received either mechanical compression or low molecular weight heparin (LMWH), they did not present the differences in incidence or VTE events.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic VCF placement was evaluated according to the guidelines of the Eastern Association for the Surgery of Trauma (EAST) [11]. In addition, the patient's risk for VTE was assessed using the RAPT score developed by Greenfield and co-workers [3] (Table 1). High-risk trauma patients (RAPT score ≥ 5) were evaluated for prophylactic VCF when pharmacologic prophylaxis for VTE was contraindicated.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence for venous thromboembolic events (VTE) varies widely in the literature from 5 to 58% [1][2][3]. In some series, PE represents the third major cause of death after trauma in those patients who survive longer than 24 h after injury [4].…”
Section: Introductionmentioning
confidence: 99%